2006
DOI: 10.1021/jp055890p
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Liquid−Vacuum Interface of Room-Temperature Ionic Liquids:  A Molecular Dynamics Study

Abstract: Molecular dynamics simulations for the liquid-vacuum interface of the ionic liquid 1-ethyl-3-methylimidazolium nitrate (EMIM+/NO3-) were performed for both electronically polarizable and nonpolarizable potential energy surfaces. The interfacial structural properties, such as the oscillation in the number density profile, the orientational ordering, and the local clustering in the interfacial region, were calculated. The simulations with both the polarizable and nonpolarizable model demonstrate the existence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

29
241
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(271 citation statements)
references
References 46 publications
29
241
0
1
Order By: Relevance
“…26 Similar gauche defect reduction was seen in SFG studies of short-to long-chain 1-alkyl-3-methylimidazolium salts at the SiO 2 interface. 116,117 The structure of the IL-vacuum interface for ͓emim͔ + / NO 3 − was reported by Yan et al 119 Surface tension and thickness of IL-vapor interfaces have been reported from both simulations 120 and experiment. 121 By accounting for both capillary waves and zero-point motions, the underlying structure of the IL surface has been determined by comparing MD simulations with x-ray reflectivity experiments.…”
Section: Il Interfacesmentioning
confidence: 67%
See 1 more Smart Citation
“…26 Similar gauche defect reduction was seen in SFG studies of short-to long-chain 1-alkyl-3-methylimidazolium salts at the SiO 2 interface. 116,117 The structure of the IL-vacuum interface for ͓emim͔ + / NO 3 − was reported by Yan et al 119 Surface tension and thickness of IL-vapor interfaces have been reported from both simulations 120 and experiment. 121 By accounting for both capillary waves and zero-point motions, the underlying structure of the IL surface has been determined by comparing MD simulations with x-ray reflectivity experiments.…”
Section: Il Interfacesmentioning
confidence: 67%
“…A wide variety of experimental, theoretical, and simulation methods have been applied to the study of ILs at interfaces. [107][108][109][110][111][112][113][114][115][116][117][118][119][120][121][122] Santos and Baldelli 112 have used interfacial sumfrequency generation ͑SFG͒ to show that at IL interfaces with gases or vacuum, alkyl chains on either the cations or the anions extend from the surface into the gas or vacuum. Rutherford backscattering spectra for the ͓bmim͔ + / ͓PF 6 ͔ − -vacuum interface also show the cation butyl group protruding from the bulk liquid into vacuum.…”
Section: Il Interfacesmentioning
confidence: 99%
“…However, using the extremely surface sensitive metastable induced electron spectroscopy (MIES) 1 we have recently also found significant hints that the alkyl-chains in [OMIm]Tf 2 N do not completely cover the surface, but the [Tf 2 N] À anion may be still present there. The former result has been supported by parallel MIES studies of T. Iwahashi et al 39 Molecular dynamics simulations of the interface between imidazolium-based ionic liquids and vacuum/air by A. S. Pensado et al, 40 T. Yan et al, 41 and C. D. Wick et al 42 have found the alkyl-chain sticking out of the surface and have found the anion, e.g. 26 Consequently, a single ion pair seems to be better applicable for larger anions than for smaller ones, which might require another approach and a single ion pair costs only adequate calculation times.…”
Section: Introductionmentioning
confidence: 80%
“…In general, these models are either Quantitative Structure Property Relationship (QSPR) correlations [6][7][8] , group contribution (GC) type [9][10][11][12][13][14][15][16] , or molecular dynamics (MD) simulations. [17][18][19][20][21][22][23] The main drawback of the QSPR and GC models is the narrow restrictions in choice of applicable compounds while the main limitation of MD simulations is the high computational demands and the need for starting geometry. 24 In this paper, we present two empirical correlations to predict melting point and viscosity of ILs in a way that does not need experimental input or tedious simulations, but rely on inputs from simple quantum chemical calculations.…”
Section: Introductionmentioning
confidence: 99%